Spatial Light Patterning of Full Color Quantum Dot Displays Enabled by Locally Controlled Surface Tailoring. Issue 9 (7th March 2018) - Kang, Han‐Lim; Kang, Jingu; Won, Jong Kook; Jung, Su‐Min; Kim, Jaehyun; Park, Chan Hyuk; Ju, Byung‐Kwon; Kim, Myung‐Gil; Park, Sung Kyu
Abstract: Quantum dot (QD) light‐emitting diodes have been intensively investigated as a future display technology owing to their outstanding optoelectronic properties such as narrow spectral bandwidths and high quantum efficiencies. Significant efforts have been made to achieve full color QD light‐emitting diodes (QLEDs) by applying various fine‐patterning technologies to active QD layers. However, the reported patterning methods generally require high processing cost and complex facilities which have limited their wide adoption in industrial‐scale display applications. In this study, a fine patterning method is presented by employing spatial light‐assisted and locally controlled surface tailoring. The chemical functionality of an interfacial polyethyleneimine (PEI) layer between ZnO and the QD layers is locally controlled by spatial light patterning (SLP), which is simultaneously used as a charge transfer layer and an anchoring agent for the selected QD nanoparticles. The versatility of this approach is demonstrated by patterning crossed stripes and multicolor QLED devices on selectively patterned PEI layers with a maximum luminescence of 1950 cd m −2 and a current efficiency of 2.9 cd A −1 . The SLP process described herein is a general approach for fabricating full color QLEDs with marginal toxicity. This process is compatible with the standard complementary metal‐oxide semiconductor (CMOS) processing technology. Abstract : By employing spatial light patterning (SLP) and locally controlled surface tailoring method, fine patterning of various quantum dot layers is successfully achieved. The chemical functionality of a polyethyleneimine layer is modified by the SLP and used simultaneously for a charge transfer layer as well as an anchoring agent for the quantum dot light‐emitting diode (QLED) devices.